2016
DOI: 10.1111/trf.13497
|View full text |Cite
|
Sign up to set email alerts
|

Erythrophagocytosis by plasmacytoid dendritic cells and monocytes is enhanced during inflammation

Abstract: The nature of APCs that consume transfused RBCs is changed by inflammation. Given that APCs initiate humoral immune responses, these findings provide potential mechanistic insight into how inflammation regulates RBC alloimmunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 44 publications
(85 reference statements)
2
52
0
Order By: Relevance
“…The identity and context of phagocytes that ingest the antigenloaded RBCs could lead to different outcomes, in terms of both antigen presentation and stimulation of an immune response (40)(41)(42). Phagocytosis triggers elaborate signals that might either induce tolerance or an immune response (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…The identity and context of phagocytes that ingest the antigenloaded RBCs could lead to different outcomes, in terms of both antigen presentation and stimulation of an immune response (40)(41)(42). Phagocytosis triggers elaborate signals that might either induce tolerance or an immune response (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Not all transfusion recipients make detectable alloantibodies to foreign RBC antigens (“non-responders”). In the absence of inflammation, mice transfused with RBCs expressing transgenic human glycophorin A (hGPA) antigen did not produce detectable anti-hGPA immunoglobulins in contrast to the same protocol in the setting of inflammation[126], perhaps due to changes in the subset of antigen presenting cells that phagocytose RBCs[127]. In fact, these mice demonstrated evidence of true immunologic tolerance in that later challenge with hGPA in the context of inflammation still did not result in an immune response.…”
Section: Effects Of Drugs On Rbcsmentioning
confidence: 99%
“…This is likely attributed to the significant changes in PRBC that occur during routine storage which result in expression of DAMP [287]. It has been reported that inflammation enhances erythrophagocytosis [91,92] and the modulation of mDC and BDCA3 + DC phenotype observed in this study, particularly in the models associated with infection processes, may be the result of increased erythrophagocytosis.…”
Section: Prbc Storage Was Associated With Increased Erythrophagocytosismentioning
confidence: 49%
“…In addition, a murine transfusion model using non-leukodepleted PRBC demonstrated CD200 + (tolerising) DC may play a role in modulating transfusion-associated tumour growth [90]. Erythrophagocytosis by murine plasmacytoid (p)DC particularly in costimulation with TLR3 agonist, polyinosinic-polycytidylic acid (polyI:C)-driven inflammation has been reported [91]. Murine studies have also demonstrated that splenic DC are important for outcomes in terms of alloimmunisation [92,93].…”
Section: In-vitro and In-vivo Models Of Prbc Transfusion (Related To mentioning
confidence: 99%
See 1 more Smart Citation